Religious Values In Mapak Dance In Baturaja Village Empat Lawang - Tiara Ansiska; Sinta Dwi Lestari; Fenti Elfina Juita; Rini Puspitasari; Resti Komala Sari (Yayasan Azhar Amanaa Yogyakarta, 2026)
Mapak Dance is a traditional welcoming dance from Baturaja Village, Tebing Tinggi District, Empat Lawang Regency, South Sumatra. The dance was inaugurated in 2007 and first performed at the inauguration of Empat Lawang Regency. The dance features movements adapted from various districts, a procession of giving betel leaves, and traditional clothing with songket motifs. The term “mapak” means to welcome with full respect. This study examines how religious values are expressed and internalized through Mapak Dance in the community of Baturaja Village. The study employs a qualitative approach with a descriptive ethnographic case study design. Data were collected through limited participatory observation, semi-structured in-depth interviews, and documentation conducted for approximately one month (February–March 2026). Findings show that Mapak Dance is consistently performed in traditional activities such as the welcoming of distinguished guests, wedding ceremonies, and official village events. The dance follows structured and hereditary procedures. Religious values embedded in the dance are reflected in the sembah (prayer) gesture through sincerity, respect, humility, and good intention. Discipline during performance is expressed through adherence to rhythm and position. Courtesy is reinforced during the betel leaf offering. Shared responsibility supports the preservation of the tradition. The study concludes that Mapak Dance functions as a social practice that strengthens religious character and social cohesion amidst modernization and globalization.